Genome sequencing and analysis uncover the regulatory elements involved in the development and oil biosynthesis of Pongamia pinnata (L.) – A potential biodiesel feedstock - Sreeharsha, Rachapudi Venkata; Mudalkar, Shalini; Reddy, Attipalli Ramachandra (Frontiers in Plant Science, 2022)
Due to rapid industrialization, consumption of petro-products has increased, while fossil fuel resources have been gradually depleted. There has been a resurgence of interest in plant-derived biofuels as a sustainable alternative to fossil fuels for the purpose of reducing greenhouse gas emissions. Milletia pinnata (formerly Pongamia pinnata L.,) is an oil-yielding, leguminous tree with a large and complex genome. Despite its multiple industrial applications, this orphan tree species has inconsistent yields and a limited understanding of its functional genomics. We assessed physiological and morphological characteristics of five high yielding pongamia accessions and deduced important yield descriptors. Furthermore, we sequenced the genome of this potential biofuel feedstock using Illumina HiSeq, NextSeq and MiSeq platforms to generate paired-end reads. Around 173 million processed reads amounting to 65.2 gb were assembled into a 685 Mb genome with a gap rate of 0.02%. The sequenced scaffolds were used to identify 30,000 gene models, 4,06,385 Simple-Sequence-Repeat (SSR) markers and 43.6% of repetitive sequences. We further analysed the structural information of genes belonging to certain key metabolic pathways, including lipid metabolism, photosynthesis, circadian rhythms, plant-pathogen interactions, and karanjin biosynthesis, all of which are commercially significant for pongamia. A total of 2,219 scaffolds corresponding to 29 transcription factor families provided valuable information regarding gene regulation in pongamia. Similarity studies and phylogenetic analysis revealed a monophyletic group of Fabaceae members wherein pongamia out-grouped from Glycine max and Cajanus cajan, revealing its unique ability to synthesize oil for biodiesel. This study is the first step toward completing the genome sequence of this imminent biofuel tree species. Further attempts at re-sequencing with different read chemistry will certainly improve the genetic resources at the chromosome level and accelerate the molecular breeding programmes.